Performing women/performing womanhood theatre, politics, and dissent in North India - Bhatia, Nandi, 1963- (New Delhi ; Oxford : Oxford University Press, 2010)
'Performing Women' brings visibility to the work of women who performed on the borderlines of dominant theatrical activity and engaged in dramatic enactments that contested middle-class codes of female propriety, which became normalised in the national popular consciousness.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women in the theater -- India, North; Women -- India, North -- Social conditions